Learning to Code: Effects of Programming Modality in a Game-Based Learning Environment - Colon-Acosta, Nirmaliz (ProQuest LLC, 2019)
As new introductory block-based coding applications for young students to learn basic computer science concepts, such as, loops and conditionals, continue to increase in popularity, it is necessary to consider the best method of teaching students these skills. Many of these products continue to exhibit programmatic misconceptions of these concepts and many students struggle with how to apply what they learn to a text-based format due to the difficulties with learning the syntactic structure not present in block-based programming languages. If the goal of teaching young students how to program is meant to develop a set of skills they may apply when learning more complex programming languages, then discerning how they are introduced to those practices is imperative. However, few studies have examined how the specific modality in which students are taught to program effects how they learn and what skills they develop. More specifically, research has yet to effectively investigate modality in the context of an educational coding game where the modality feature is controlled, and content is consistent throughout game-play. This is mainly due to the lack of available games with this feature designed into the application. This dissertation explores whether programming modality effects how well students can learn and transfer computer science concepts and practices from an educational programming game. I proposed that by being guided from a blocks-based to text-based programming language would instill a deeper understanding of basic computer science concepts and would support learning and improve transfer and performance on new challenging tasks. Two experimental studies facilitated game-play sessions on the developed application for this project. The first study was a 2x2 between subjects design comparing educational module (game versus basic) and programming modality (guided versus free choice). The findings from Study 1 informed the final version design for the module used in the second study where only the game module was used in order to focus the comparison between programming modality. Findings showed that students who coded using the game module performed better on a learning test. Study 2 results showed that students who are transitioned from blocks-based to text-based programming language learn basic computer science concepts with greater success than those with the free choice modality. A comparative study was conducted using quantitative data from learning measures and qualitative video data from the interviews during the challenge task of the second study. This study examined how students at the extreme levels of performance utilized the toggle switch feature during game-play and how the absence of the feature impacted how they completed the challenge task. This analysis showed two different methods of toggle switch usage being implemented by a high and low performing student. The high performing student utilized the resources more often during the challenge tasks in lieu of leveraging the toggle switch and were still able to submit high level code. Results suggest that a free choice student who uses the feature as a tool to check their prewritten code rather than a as short cut for piecing code together as blocks and submitting the text upon the final attempt. This practice leads to a shallower understanding of the basic concepts and make it extremely difficult to expand and apply that knowledge to a more difficult task. This dissertation includes five chapters: an introduction and theoretical framework, a game design framework and implementation description, two experimental investigations, and a quantitative and qualitative comparative analysis. Chapter one provides the conceptual and theoretical framework for the two experimental investigations. Chapter two describes the theory and design structure for the game developed for this dissertation work. Chapter three and four will discuss the effects of programming modality on learning outcomes. Specifically, chapter 3 focuses on implications of programming modality when determining how to implement changes for the design of the game for Study 2. Chapter five discusses a comparative analysis that investigated differing work flow patterns within the free choice condition between high and low performing students. Results from these three chapters illustrate the importance of examining this component of the computer science education process in supplemental games for middle and high school students. Additionally, this work contributes in furthering the investigation of these educational games and discusses implications for design of similar applications. [The dissertation citations contained here are published with the permission of ProQuest LLC. Further reproduction is prohibited without permission. Copies of dissertations may be obtained by Telephone (800) 1-800-521-0600. Web page: http://www.proquest.com/en-US/products/dissertations/individuals.shtml.]